The post-Newtonian motion around an oblate spheroid: the mixed orbital effects due to the Newtonian oblateness and the post-Newtonian mass monopole accelerations - Iorio, Lorenzo (General relativity and gravitation, 2023)
When a test particle moves about an oblate spheroid, it is acted upon, among other things, by two standard perturbing accelerations. One, of Newtonian origin, is due to the quadrupole mass moment J 2 of the orbited body. The other one, of order O 1 / c 2 , is caused by the static, post-Newtonian field arising solely from the mass of the central object. Both of them concur to induce indirect, mixed orbital effects of order O J 2 / c 2 . They are of the same order of magnitude of the direct ones induced by the post-Newtonian acceleration arising in presence of an oblate source, not treated here. We calculate these less known features of motion in their full generality in terms of the osculating Keplerian orbital elements. Subtleties pertaining the correct calculation of their mixed net precessions per orbit to the full order of O J 2 / c 2 are elucidated. The obtained results hold for arbitrary orbital geometries and for any orientation of the body’s spin axis k ^ in space. The method presented is completely general, and can be extended to any pair of post-Keplerian accelerations entering the equations of motion of the satellite, irrespectively of their physical nature.